Electrohydrodynamic printing of a dielectric elastomer actuator and its application in tunable lenses. (August 2021) - Jiang, Liang; Wang, Yuhao; Wang, Xueqin; Ning, Fanggang; Wen, Shipeng; Zhou, Yanfen; Chen, Shaojuan; Betts, Anthony; Jerrams, Stephen; Zhou, Feng-Lei
Abstract: Optical lenses driven by dielectric elastomer (DE) actuators with tunable focal lengths are presented here. They are inspired by the architecture of the crystalline lens and the ciliary muscle of the human eye and have prompted a growing interest. The most commonly used DEs in tunable lenses have often required highly transparent films and also the need to encapsulate clear liquid silicone to act as the lens. There is a restriction on the properties of the tunable lens imposed by materials limitations. Here, the fabrication of a fully 3D printed tunable lens with an inhomogeneous structure is described. It exhibited a 29% change in focal length from 33.6 mm to 26.1 mm under a dynamic driving voltage signal control. Furthermore, it displayed excellent stability when the focal length was tuned from far to near (30.1 mm to 25.3 mm) for 200 cycles. The tunable lens obtained mimics the working principle of the human eye in auto adjusting the focal length and has evident potential applications in imaging, information storage, beam steering and bifocal technology.